Poetry Musicalization Assistance for Middle School Students in East Penfui Village - Karolus Budiman Jama; Margaretha P.E. Djokaho (Jurnal Pengabdian Masyarakat Bestari, 2022)
This article discusses poetry musical assistance for junior high school students in East Penfui village. During the Covid-19 pandemic, these junior high school students carried out learning activities from home. When they enter a normal situation, they return to school. The problem that arises is that students do not immediately adapt to the school environment. The important thing in this community service program is first, the achievement of solutions to partner problems, namely students can adapt quickly in the face-to-face (offline) learning process. Second, the continuation of the community service program supports partner programs in art training for female students around Penfui Timur Village. This training activity has helped students grow their abilities in the arts.